2010
DOI: 10.1186/1471-2164-11-352
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel splice array platform and its application in the identification of alternative splice variants in lung cancer

Abstract: BackgroundMicroarrays strategies, which allow for the characterization of thousands of alternative splice forms in a single test, can be applied to identify differential alternative splicing events. In this study, a novel splice array approach was developed, including the design of a high-density oligonucleotide array, a labeling procedure, and an algorithm to identify splice events.ResultsThe array consisted of exon probes and thermodynamically balanced junction probes. Suboptimal probes were tagged and consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 59 publications
1
19
0
1
Order By: Relevance
“…Dysregulation of melanophilin was found in several types of tumors, e.g. lung cancer, meningiomas and breast cancer (Fevre-Montange, et al, 2009; Molina-Pinelo, et al, 2014; Pio, et al, 2010; Thakkar, et al, 2010). A very recent study found association of expression of MLPH (and some other genes) with nearby SNPs in prostate tissue (Penney, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of melanophilin was found in several types of tumors, e.g. lung cancer, meningiomas and breast cancer (Fevre-Montange, et al, 2009; Molina-Pinelo, et al, 2014; Pio, et al, 2010; Thakkar, et al, 2010). A very recent study found association of expression of MLPH (and some other genes) with nearby SNPs in prostate tissue (Penney, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis could therefore determine additional regulatory targets (see Supplemental Discussion). To this end, we compiled a list of 54 experimentally validated alternative splicing events shown to undergo a splicing pattern change in colon tumor samples compared with corresponding normal tissue samples (Jordan et al 1999;Hardt et al 2003;Ghigna et al 2005;Gardina et al 2006;Klinck et al 2008;Thorsen et al 2008;Venables et al 2009;Langer et al 2010;Misquitta-Ali et al 2010;Pio et al 2010;Choi et al 2011;Ishimoto et al 2011;Liu et al 2012;Miura et al 2012;Seo et al 2012). We then identified the potential regulators of these cancerous splicing changes by the number and strength of determined Pearson correlations between the splicing changes of the 54 alternative events across 48 human tissues and cell lines and the gene expression of alternative splicing factors in the same tissues (Methods).…”
Section: In Silico Identification Of Colon Cancer Alternative Splicinmentioning
confidence: 99%
“…The Pearson correlations between the splicing profiles of 54 cancer-associated alternative splicing events (Jordan et al 1999;Hardt et al 2003;Ghigna et al 2005;Gardina et al 2006;Klinck et al 2008;Thorsen et al 2008;Venables et al 2009;Langer et al 2010;Misquitta-Ali et al 2010;Pio et al 2010;Choi et al 2011;Ishimoto et al 2011;Liu et al 2012;Miura et al 2012;Seo et al 2012) across all tissues and the gene expression profiles of alternative splicing factors (gene list derived from Manley 2009 andHegele et al 2012) in the same tissues were computed (alternative splicing and gene expression data were derived from Castle et al 2008). Alternative splicing factor genes not displaying a significant expression level change in colon tumors compared with a mixed tissue pool were discarded as were splicing events with significant isoform changes compared with a mixed tissue pool in only four tissues or less, and statistically insignificant correlations (P > 0.05).…”
Section: In Silico Identification Of Colon Cancer Alternative Splicinmentioning
confidence: 99%
“…The former were developed by Oryzon Genomics in collaboration with our group, and have been previously described (27). These arrays contain exon probes and thermodynamically balanced junction probes.…”
Section: Microarray Hybridizationmentioning
confidence: 99%
“…These high-density arrays contain an average of 8 probes per probeset. RNA labeling and hybridization on the Agilent microarrays were performed by Oryzon Genomics, as previously described (27). Labeling and hybridization on the Affymetrix GeneSplice microarrays were performed by the Proteomics, Genomics and Bioinformatics Core Facility of the Center for Applied Medical Research (CIMA) following manufacturer's instructions.…”
Section: Microarray Hybridizationmentioning
confidence: 99%